Shear and compression characteristics of peanut vines based on response surface methodology - Chen, Yong; Mao, Ruonan; Zhang, Xiuli; Ma, Hao; Li, Bingjun; Hu, Bin; Luo, Xin; Zhao, Jiahui; Liu, Xiaochan (International Journal of Agricultural and Biological Engineering, 2026)
To address issues such as incomplete shredding and high energy consumption during peanut vine processing, this study investigated the mechanical properties of peanut vines. This study employed the response surface methodology to systematically investigate the shear and compressive mechanical properties of peanut vines under varying sampling locations, loading rates, and moisture contents. The results indicated that the root base of peanut vines exhibited the strongest shear and compressive resistance, with an average maximum shear force of 46.44±1.70 N, ultimate load of 26.90 N, fracture strength of 0.39 MPa, and elastic modulus of 3.52 MPa. A novel finding is the bimodal characteristic of the shear force-displacement curve, indicating two distinct failure stages involving both the rind and the pith cavity. Furthermore, moisture content negatively correlates with shear strength. Response surface analysis revealed that both shear location and moisture content significantly affected the shear force of peanut vines, with shear location having the most pronounced influence. Within the quasi-static loading range examined, the shear force reached its maximum when the cutting point was at the root, the loading speed was 40 mm/min, and the moisture content was 30% for peanut vines. This study provides a theoretical basis and benchmark data support for the development of efficient peanut vine shredding technology. Key words: peanut vines; shear force, compression characteristics; mechanical properties; Box-Behnken response surface analysis DOI: 10.25165/j.ijabe.20261904.10439 Citation: Chen Y, Mao R N, Zhang X L, Ma H, Li B J, Hu B, et al. Shear and compression characteristics of peanut vines based on response surface methodology. Int J Agric & Biol Eng, 2026; 19(4): 328–337.